The Effect of Emotional Intelligence and Independent Learning on Students' Creative Thinking Ability - Wahyuddin Wahyuddin; Ifa Umiah; Andi Quraisy (Postgraduate, University of Mataram, 2023)
This study aims to analyze the level of emotional intelligence and learning The research variables consist of independent variables, namely emotional intelligence and learning independence, while the dependent variable is the ability to think creatively. The instrument for measuring the independent variables is an emotional intelligence questionnaire consisting of 20 question items developed from 5 indicators, namely recognizing emotions, managing emotions, motivating oneself, recognizing other people's feelings, and building relationships; the self-learning questionnaire consists of 20 question items developed from 5 indicators namely initiative, self-confidence, motivation, discipline, and responsibility; while the dependent variable is measured by a test of 4 questions created from four aspects, namely fluency, flexibility, originality, and elaboration. The questionnaire and test fulfill the validity and reliability tests. The data were processed by descriptive and inferential analysis through multiple regression analysis with the SPSS version 23 program. The study's results concluded that emotional intelligence and independent learning simultaneously affect students' creative thinking ability, with an effect is 59.7%. Partially the influence of emotional intelligence on the results of the ability to think creatively is 36.3%, and the impact of independent learning on the ability to think creatively is 9.5%. It means that the higher the emotional intelligence and learning independence students possess; their learning outcomes increase. Thus, to improve students' creative thinking abilities, emotional intelligence and learning independence must be improved first.